Synthesis and Characterization of Mannosylated Formulations to Deliver a Minicircle DNA Vaccine - Ana Sofia Serra; Dalinda Eusébio; Ana Raquel Neves; Tânia Albuquerque; Himanshu Bhatt; Swati Biswas; Diana Costa; Ângela Sousa (Pharmaceutics, 2021)
DNA vaccines still represent an emergent area of research, giving rise to continuous progress towards several biomedicine demands. The formulation of delivery systems to specifically target mannose receptors, which are overexpressed on antigen presenting cells (APCs), is considered a suitable strategy to improve the DNA vaccine immunogenicity. The present study developed binary and ternary carriers, based on polyethylenimine (PEI), octa-arginine peptide (R8), and mannose ligands, to specifically deliver a minicircle DNA (mcDNA) vaccine to APCs. Systems were prepared at various nitrogen to phosphate group (N/P) ratios and characterized in terms of their morphology, size, surface charge, and complexation capacity. In vitro studies were conducted to assess the biocompatibility, cell internalization ability, and gene expression of formulated carriers. The high charge density and condensing capacity of both PEI and R8 enhance the interaction with the mcDNA, leading to the formation of smaller particles. The addition of PEI polymer to the R8-mannose/mcDNA binary system reduces the size and increases the zeta potential and system stability. Confocal microscopy studies confirmed intracellular localization of targeting systems, resulting in sustained mcDNA uptake. Furthermore, the efficiency of in vitro transfection can be influenced by the presence of R8-mannose, with great implications for gene expression. R8-mannose/PEI/mcDNA ternary systems can be considered valuable tools to instigate further research, aiming for advances in the DNA vaccine field.